Improvement Model for Inventory Management with the use of the ABC Classification, Economic Lot (EOQ) and Reorder Point (ROP) in a tire retailing company - Comitre Cornejo, Ilan Daniel (2024)
The global tire marketing sector faced disruptions due to the pandemic, affecting production and demand.The recovery, driven by economic revival and increased vehicle demand, especially in strategic countries like China, the US, and the EU, is evident.In Peru, the tire trade sector mirrors global trends, with sustained growth linked to increased car sales.The investigated company, operating for over two decades, engages in stores, distribution, fleet, and web businesses.85% of purchases come from foreign suppliers, mainly Brazil and Germany.Despite pandemic challenges, the company maintained and exceeded pre-pandemic sales since August 2021.However, inventory management remains a challenge, impacting customer satisfaction and sales.This research project aims to demonstrate that implementing an inventory management improvement model enhances company productivity and efficiency.Specific objectives include reviewing supply management in Peru's tire sector, analyzing inventory management issues, proposing engineering-based solutions, and validating the proposed solution's economic feasibility.Some of the most significant results obtained include a 30.6% improvement in total logistic costs, a 15% enhancement in average customer response time, and a current net benefit of approximately $200,000.Focusing on light vehicle tire sales, the project employs a correlational-descriptive approach with experimental design to manipulate independent variables.Limitations include data collection challenges from the company and infrequent analysis of inventory-related procedures.Key performance indicators (KPIs) like high inventory turnover, idle inventory, and total logistic cost are identified as challenges.The project addresses these challenges to enhance operational efficiency and company profitability. © 2024 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.